THE SIGNIFICANCE OF THE BOOK IN THE MODERN WORLD (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Book of a person internal the world enriches This is life all stages important important owner , this is both an assistant , and a consultant , and entertainment . Books forever , but the Internet is forever it's not . Powers Internet and electricity off to put can People and country paralyzed will be , life stops . Whose if he has a " key " in his hand , that is the country to the hand in getting problem no . From the day to the day people book study stop are going - this while is a tragedy . Not only that people , maybe some of states their own governments state citizen for of the book importance does not understand